Analisis Hedonisme Iklan M-Banking BRImo di Televisi Amanda Rawles - Mutimmah, Nihayatul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
In this digital era, every company or producer in making advertisements has to have more creative advertising innovations so that the product message conveyed effectively and efficiently reaches all levels of society. This research is to analyze the creative message strategy and message appeal in the Amanda Rawles edition of the BRImo advertisement on television with an emphasis on the element of hedonism. The object of this research is the